ALICE IN WONDERLAND SYNDROME IN THE LIGHT OF THE LATEST REPORTS – A LITERATURE REVIEW - Karolina Oskroba; Maciej Sokołowski; Joanna Kryślak; Adam Solarz; Szymon Szabelski (International Journal of Innovative Technologies in Social Science, 2025)
Alice in Wonderland Syndrome (AIWS) was first described in 1955 by British psychiatrist John Todd, hence it is also known as Todd’s syndrome. The name of the disorder refers to Lewis Carroll’s novel Alice in Wonderland, whose author, who probably suffered from migraines with aura, may have been inspired by his own experiences with perceptual disturbances. AIWS is a rare, complex sensory perception disorder that lies at the intersection of neurology and psychiatry. The syndrome is characterized by transient, reversible distortions in the perception of space, time, movement, and one’s own body image. These episodes are usually short-lived, lasting from a few minutes to several hours, and in most cases are completely reversible. The aim of this literature review was to present the current state of knowledge on AIWS, with particular emphasis on its etiology, symptomatology, pathophysiological mechanisms, diagnostic methods, and therapeutic options. The analysis also included studies comparing AIWS with other conditions with similar clinical presentations, such as migraine with aura, temporal lobe epilepsy, and schizophrenia. Contemporary research emphasizes the importance of transient disturbances in brain bioelectrical activity and abnormalities in blood flow in the occipital and temporal lobes in the pathogenesis of AIWS. Treatment is causal and focuses on the underlying disease. Alice in Wonderland syndrome, despite its rarity, is a fascinating example of the interaction between human perceptual, cognitive, and neurological processes. The increase in the number of scientific publications in recent years indicates a growing interest in this syndrome, but the limited number of studies on its mechanisms highlights the need for further interdisciplinary research collaboration.